Microfluidic one-step synthesis of a metal−organic framework for osteoarthritis therapeutic microRNAs delivery - Yang, Kaiyuan; Ni, Min; Xu, Chao; Wang, Liangliang; Han, Long; Lv, Songwei; Wu, Wenbo; Zheng, Dong (Frontiers in Bioengineering and Biotechnology, 2023)
As a class of short non-coding ribonucleic acids (RNAs), microRNAs (miRNA) regulate gene expression in human cells and are expected to be nucleic acid drugs to regulate and treat a variety of biological processes and diseases. However, the issues with potential materials toxicity, quantity production, poor cellular uptake, and endosomal entrapment limit their further applications in clinical practice. Herein, ZIF-8, a metal-organic framework (MOF) with noncytotoxic zinc (II) as the metal coordination center, was selected as miRNA delivery vector was used to prepare miR-200c-3p@ZIF-8 in one step by Y-shape microfluidic chip to achieve intracellular release with low toxicity, batch size, and efficient cellular uptake.